Depression in Elderly Patients Attending the Psychiatric Outpatient Department: A Cross Sectional Study - Sharma, Dr. Ravi C; Sharma, Dr. Dinesh Dutt; Parkash, Dr. Kamal (International Journal of Innovative Research in Medical Science, 2018)
Background: Cognitive impairment is a common clinical condition among elderly patients suffering with depression and has a well-known aetiology. The present study planned to determine the prevalence of cognitive impairment and depression in geriatric patients attending Psychiatric outpatient department services. Methods: The study was a prospective cross-sectional one and carried out with a sound methodology on elderly patients attending the Psychiatric OPD of Indira Gandhi Medical College, Shimla-1, Himachal Pradesh. A total of 130 patients were screened, out of which 105 patients have fulfilled the inclusion criteria and enrolled after written informed consent form. The cognitive function and depression were assessed by using standardized Mini-Mental State Examination of Folstein (MMSE) and the Geriatric Depression Scale (GDS), respectively. Results: Prevalence of cognitive impairment was found 42.9% (44.2% in women, 35.5% in men), whereas the prevalence of depression was found 48.6% (56.30%women, 41.10% men) which was statistically significant (p<0.05).Conclusions: Cognitive impairment and depression were found to be more prevalent in the females than in the males. So, it is advised that psychiatrist should provide special attention for early detection and treatment of depressive symptoms in elderly patients suffering with cognitive impairment.